Combining Syntactic Analysis and Autoethnography in developing accounting graduates employability skills - Abdul Aris, Nooraslinda; Amirrudin, Mira Susanti; Mahmood, Anisah (Academica Press Solutions, 2024)
Findings suggest that there needed to be a better match between labour expectations and graduates produced by Higher Learning Institutions (HLIs), which resulted in excess numbers of highly trained graduates in the labour force. As such, this study focuses on collecting and understanding the necessary employability skills that enable graduates to be hired by businesses using Syntactic Analysis. To be more precise, the study looks at accounting graduates as the need for the profession evolved. Changes in accounting education are considered critical to ensure the development of appropriate skills, knowledge, and attitudes among accounting graduates. In developing the appropriate skills, the study adopted autoethnography by considering three prominent actors – the employer, faculty, and graduates. The actors' viewpoints were compared to spot any needs to enhance or change the current curriculum. The findings of the study are hoped to provide insight into employability skills deemed significant and will provide guidance to HLIs to come up with a broad skill base for fresh accounting graduates to prepare them for the volatile business environment and encourage life-long learning to remain relevant and valuable to the industry.